(untitled) (Journal of actual problems of jurisprudence, 2018)
This article provides a description of the basic rules governing the conditions of the fulfillment of obligations in the Republic of Kazakhstan. As a result of analysis, the author observes the principles, object, place, time and methods of performance. Key words: obligation, fulfillment of obligation, pecuniary obligation, object of fulfillment of obligation, methods of performance of obligations.